YOUTH KNOWLEDGE ABOUT THE GENERATION PLANNING PROGRAM AND ATTITUDE OF YOUTH IN MATURITY AGE OF MARRIAGE AT SMA NEGERI 4 BATAM - Acholder Tahi Perdoman; Dewi Fitriana (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Background : Generation Planning is a program developed in the context of preparing and planning family life for adolescents. One of the main focuses in this program is the maturity of marriage age for adolescents. The purpose of this study was to describe the knowledge of adolescents about the Generation Planning program and the attitudes of adolescents in the maturity of the marital age at SMA Negeri 4 Batam. Method : This study used a descriptive research design. The length of the research was 6 months with a population of all students of class X and XI SMA N 4 Batam as many as 737 students, the sampling was systematic random sampling with a sample size of 88 respondents. , Result : as many as 53 respondents (60.2%) and good as many as 35 respondents (39.8%). Frequency distribution of the majority of adolescents' attitudes have positive attitudes as many as 63 respondents (71.6%) and those who have negative attitudes are 25 respondents (28.4%) conclusion : Adolescent knowledge about the Planning Generation program at SMAN 4 Batam is the majority of the knowledge is Less as many as 53 respondents (60%) The attitude of adolescents in the Maturity of the Marriage Age at SMAN 4 Batam is that the majority are positive as many as 63 respondents (71%)